2001
DOI: 10.1007/3-540-45307-5_29
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Mobile Agents for E-commerce Applications

Abstract: Abstract. Mobile agents are emerging as a promising paradigm for the design and implementation of distributed applications. While mobile agents have generated considerable excitement in the research community, they have not translated into a significant number of real-world applications. One of the main reasons for this is the lack of work that quantitatively evaluates ( i) the effectiveness of one mobile agent framework over another, and (ii) the effectiveness of mobile agents versus traditional approaches. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…However, our proposed query retrieval approach is different compared with the previous approaches [15][16][17]19,20,23,18] object cloning, dispatching, and disposing. This is done by combining a hierarchical and a parallel dispatching of mobile agents to the LP servers in order to retrieve the query results which has been applied in the EHQR approach as described in Section 4.6.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, our proposed query retrieval approach is different compared with the previous approaches [15][16][17]19,20,23,18] object cloning, dispatching, and disposing. This is done by combining a hierarchical and a parallel dispatching of mobile agents to the LP servers in order to retrieve the query results which has been applied in the EHQR approach as described in Section 4.6.…”
Section: Discussionmentioning
confidence: 92%
“…We try to minimize the number of agents used to fetch the query results from the remote hosts in order to reduce network overload. It is different compared with the previous approaches [15][16][17][18][19][20]23,24,[26][27][28] by utilizing the mobile agent properties such as object cloning, dispatching, and disposing in the EHQR approach. This is done by combining a hierarchical and a parallel dispatching of mobile agents to the local prefetch servers in order to retrieve the query results in the MaSS.…”
Section: Related Work On Mobile Agents For Query Retrievalmentioning
confidence: 97%
See 1 more Smart Citation
“…It does not accept inputs from the user. Also it has been noted that adoption of Agent technology in real world applications is very slow though it has many advantages such as reduced network load, overcoming network latency etc., [16][17][18]. Also it has been shown that mobile Agent technology is a better alternative to Client/server architecture [17].…”
Section: Agent Based Mobile Shopper-our Proposalmentioning
confidence: 97%
“…With the concept of mobile agent, the execution process will go to the place where the data are available, data will not send to the place of execution process. For this process mobility, different types (Jha and Iyer, 2001) of mobile agents are developed with different standards and procedures. The different type of agents are: Single hop mobile agent (will visit only one remote host and get back to home), Multihop mobile agent with Static Itinerary and Static Order (will visit multiple remote host and return to the owner with the required result.…”
Section: Introductionmentioning
confidence: 99%